Paul Auster, Report from the Interior.“From you to you, and conversely” - Jean-Louis CLARET (E-REA)
In Report from the Interior by Paul Auster the personal pronoun you is used in an unconventional manner as it places the readers in a position that is both uncomfortable and delightful. As a matter of fact, this unconventional process causes the narrator and the reader to coalesce and to share a common life experience that they either piece together through remembering or discover through reading. The embedded narratives that stud this text put the finishing touch to the disorientation of the readers who follow an ethereal guide. The presence of a series of photographs at the end of the book provides a different and complementary point of view that prompts a subtle dialogue between text and image. Though the protagonist is never represented, the gaze he included in the text may be interpreted as some form of incarnation that strengthens the link between the narrator and the reader.